(untitled) (Texas Journal of Engineering and Technology, 2022)
Crisply gathered Jerusalem tubers contain inulinase, a protein that requires inactivation, since of its capacity to hydrolysis inulin into fructose, which can be devoured by microorganism amid marinating. As the traditional pickling process takes 6 months, and involves the addition of a large amount of salt (18–20%), this production strategy is uneconomical and increases the nitrite intake. Additionally, miscellaneous bacteria produced during pickling affect the product taste. In this study, the enzyme inactivation effects of NaCl, NaHCO3, and ultrasound were evaluated. NaHCO3 treatment results in the highest degree of enzyme inactivation; however, the quality and flavor of the obtained Jerusalem tubers pickles were not ideal. The Jerusalem tubers pickles in which the enzymes were inactivated using a combination of NaCl and ultrasound exhibited better flavor than those exposed to NaHCO3; further, this combination reduced the inulinase activity of the Jerusalem tubers to 2.50 U/mL, and maintained the inulin content at 61.22%. The strains LS3 and YS2, identified as Enterococcus facials and the salt-tolerant yeast respectively, were the dominant microorganisms isolated from the pickle juice. Jerusalem tubers with inactivated inulinase were pickled with microbial powder, separated, purified, and dried to remove the natural Jerusalem tubers sauce. This process shortened the fermentation cycle and improved product quality